2004
DOI: 10.1080/09638230400017020
|View full text |Cite
|
Sign up to set email alerts
|

A survey of clinical psychologists' views regarding service user involvement in mental health services

Abstract: Background: The current study was concerned with the issue of service user involvement in the planning and running of mental health services within the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 5 publications
2
39
1
3
Order By: Relevance
“…The original CPQ consists of 20 items with 14 items referring to 'Yes', 'No', or 'Don't know' response categories; 4 referring to a 5-point Likert type scale; and 2 items provide 6 or 8 specific options (Soffe et al 2004;Kent and Read 1998). ''In order to obtain information on consumer involvement at all levels of service delivery items were designed to cover treatment, evaluation, planning, and management.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The original CPQ consists of 20 items with 14 items referring to 'Yes', 'No', or 'Don't know' response categories; 4 referring to a 5-point Likert type scale; and 2 items provide 6 or 8 specific options (Soffe et al 2004;Kent and Read 1998). ''In order to obtain information on consumer involvement at all levels of service delivery items were designed to cover treatment, evaluation, planning, and management.…”
Section: Methodsmentioning
confidence: 99%
“…Explore Norwegian CAMHS staff attitudes towards user involvement (mandated by the government's strategic plan for the development of Norwegian CAMHS.) This follows from the suggestion of Soffe et al (2004) and Kent and Read (1998) who found a dearth of research on mental health professionals' attitudes. This lack of research is particularly true in the CAMHS setting where no data is available.…”
Section: User Involvement In Norwegian Child and Adolescent Mental Hementioning
confidence: 96%
See 3 more Smart Citations